Zur Leistung der Attributsmetapher bei der Konzeptualisierung der Parlamentswahlen 2023 in Polen am Beispiel der deutschen und polnischen Online-Informationspresse - Marta Anna Gierzyńska (Beiträge zur Allgemeinen und Vergleichenden Sprachwissenschaft)
Language activity, and thus broadly understood linguistic communication, occurs on various levels and using diverse linguistic means. One of these tools is metaphor, the use of which helps in better visualization, and subsequently in the reception and understanding of abstract content. This statement also applies to issues within the realm of politics. This article analyzes the role of conceptual metaphor (cf. Lakoff/Johnson 1980), based on opposites (e.g., dark-light, cold-warm, strong-weak etc.), and points out its presence and significance in conceptualizing political struggle. The research material consists of articles from Polish and German online platforms, whose articles address the topic of parliamentary elections in Poland in 2023. The aim of the study is to answer the question of whether concepts expressed in the form of opposites can adequately capture the complexity of this problem. In the theoretical part of the article, we find a characteristic of conceptual metaphor and a description of its functions in press communications.